2017
DOI: 10.1101/188391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic and vascular inflammation in an in-vitro model of central obesity

Abstract: Metabolic disorders due to over-nutrition are a major global health problem, often associated with obesity and related morbidities. Obesity is peculiar to humans, as it is associated with lifestyle and diet, and so difficult to reproduce in animal models.Here we describe a model of human central adiposity based on a 3-tissue system consisting of a series of interconnected fluidic modules. Given the causal link between obesity and systemic inflammation, we focused primarily on pro-inflammatory markers, examinin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Neutrophil-to-lymphocyte ratio represents a rapidly accessible and inexpensive marker derived from values of a routine hemogram, which has shown to correlate with systemic inflammation in critical ill patients, chronic low-grade inflammation, accumulation of lipids in the vascular wall and atherogenic mechanisms. 24,31,32 Our results provide new insights on the NLR, potential interacting factors and sources, which may drive to atherogenesis. We found that NLR positively correlated with hsCPR, TNF-α, IL1β, adiposity indicators, leptin, and negatively correlated with adiponectin.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Neutrophil-to-lymphocyte ratio represents a rapidly accessible and inexpensive marker derived from values of a routine hemogram, which has shown to correlate with systemic inflammation in critical ill patients, chronic low-grade inflammation, accumulation of lipids in the vascular wall and atherogenic mechanisms. 24,31,32 Our results provide new insights on the NLR, potential interacting factors and sources, which may drive to atherogenesis. We found that NLR positively correlated with hsCPR, TNF-α, IL1β, adiposity indicators, leptin, and negatively correlated with adiponectin.…”
Section: Discussionmentioning
confidence: 82%
“…Neutrophil‐to‐lymphocyte ratio represents a rapidly accessible and inexpensive marker derived from values of a routine hemogram, which has shown to correlate with systemic inflammation in critical ill patients, chronic low‐grade inflammation, accumulation of lipids in the vascular wall and atherogenic mechanisms …”
Section: Discussionmentioning
confidence: 99%
“…In particular, two different environmental conditions were used: the apical side of the LiveBox2 chamber was filled with the SH-SY5Y medium, whereas the basal compartment was filled with the HCASMC medium. This is an innovative feature since, in general, a multi-organ approach needs to previously characterize the potential common medium, which has to be compatible with all the tissues within the pathway [ 16 ]. This process forces the cells to adapt to a novel environmental condition that is not the best option for them; therefore, this could cause a change in their behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Such partial insight into disease aetiopathogenesis provides one of the limitations that aw our study. To overcome this critical issue, we are implementing a dynamic in vitro model that envisages multiple bioreactors for 3D cell cultures interconnected by a dynamic ow in order to mimic the cell crosstalk that characterizes SSc pathogenesis in humans [50]. Another major limitation of this study relates to the scarce number of samples for each autoantibody speci city; unfortunately, the recruitment of a broader cohort of patients is prevented by the relative rarity of certain antibodies (e.g., ARA and anti-Th/To) in the Italian SSc population [51].…”
Section: Discussionmentioning
confidence: 99%